POLYCHLORINATED DIBENZODIOXINS (PCDDs) AND FURANS (PCDFs) AND THEIR IMPORTANCE IN MILK AND MILK PRODUCTS - Oğuz GÜRSOY (Pamukkale University Journal of Engineering Sciences, 2001)
Polychlorinated dibenzodioxins (PCDDs) and furans (PCDFs), by product of chlorinated chemical compounds production and chemical processes including combustion, are virtually ubiquitous in the environment. Because of this, PCDDs and PCDFs occur potantial risk for human health. PCDDs and PCDFs are known to exist at higher levels in fatty foods such as full-fat milk and dairy products, meat and eggs. They can accumulate in the fatty tissues of animals and humans. In this review, structure, contamination sources, toxic effects of PCDDs and PCDFs, milk, dairy products and mother's milk as contamination source and preventive measures against PCDDs and PCDFs were discussed.